Assessment of the start-up process of anaerobic digestion utilizing swine manure: 13C fractionation of biogas and microbial dynamics - Lv, Zuopeng; Liang, Jiazhuo; Chen, Xin; Chen, Zhongbing; Jiang, Jihong; Loake, Gary J (Environmental science and pollution research international, 2019)
The aim of this study was to investigate how the microbial community structure adapts during the start-up phase and how the 13C fractionation of biogas reflects the microbial population dynamics in two parallel swine manure-fed anaerobic digesters. Two swine manure-fed reactors for the start-up of continuously stirred tank reactors at mesophilic condition were evaluated. Changes in community structure were monitored using 16S rRNA high-throughput sequencing to measure the abundance of fermenting bacteria and methanogens. Digesters with relatively stable Methanosarcinaceae started up successfully and contained high gas production and low levels of propionate. In contrast, the digester that experienced a difficult start-up period had reduced Methanosarcinaceae along with accumulated propionate and low gas production. Specific gas production, specific methane production, and 13C fractionation of biogas were influenced significantly by Methanosarcinaceae, Methanobacteriaceae, and Clostridiaceae, indicating that the 13C fractionation of biogas had significant potential to reflect microbial population changes and digester performance during the start-up period.
Keywords: RNA ribozomální 16S; Biofuels; Chemical Fractionation; hnůj; prasata; Bacteria; anaerobióza; uhlík; biopaliva; Carbon; bioreaktory; Fermentation; RNA, Ribosomal, 16S; Swine; Manure; Anaerobiosis; zvířata; Animals; Bioreactors; chemická frakcionace; fermentace